Faktor-Faktor yang Mempengaruhi Implementasi Transaksi Non Tunai dan Dampaknya Terhadap Efisiensi Kerja Organisasi pada Pemerintah Daerah Kabupaten Pelalawan - Nopeanti, Ika Luly; Sari, Ria Nelly; Nasrizal, Nasrizal (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
This study aims to analyze the Factors Influencing the Implementation of Non-Cash Transactions and Its Impact on Organizational Efficiency in the Regional Government of Pelalawan Regency. The population in this study consists of all Regional Apparatus Organizations (OPDs) in Pelalawan Regency, totaling 40 OPDs. In this research, the researcher distributed 4 questionnaires to each OPD, totaling 160 questionnaires. The sample was selected using the saturated sample technique (nonprobability sampling) with respondents being Budget Users/Authorized Budget Users, Treasurers, Financial Arrangement Officers, and PPTK. Data analysis was performed using the data analysis method applied in this study, using Smart PLS version 4.0 application. he results of the study indicate that organizational commitment, regulations, human resource competency, and information technology influence the implementation of non-cash transactions in the Regional Government of Pelalawan. The implementation of non-cash transactions has a positive and significant impact on organizational efficiency. With the implementation of non-cash transactions, efficiency becomes a definite condition. This is evident in terms of time, accuracy, and the minimization of financing because, fundamentally, non-cash transactions are intended to simplify and expedite the work of the regional government.